Assessment of predictors and prognostic factors for locoregional recurrent breast cancer - Elfol, Hossam A.; Rageh, Tarek M.; Hamed, Mohammed A. (International Surgery Journal, 2018)
Background: Assessment of predictors and prognostic factors of locoregional recurrent breast cancer will help in management of those patients. The aim of this study was to assess and identify the predictors and prognostic factors for locoregional current breast cancer. Methods: This prospective study will be carried out on 50 female patients with history of breast cancer underwent surgical procedures either modified radical mastectomy (MRM) or conservative breast surgery (CBS) and adjuvant therapy (chemotherapy, radiotherapy, hormonal therapy). Results: Significant relationship between recurrence of breast cancer and Oral contraceptive pills of the studied female patients with history of breast cancer underwent surgery. Conclusions: Number of positive lymph nodes, lympho-vascular invasion, positive safety margin and presence of extensive intra-ductal component all these factors increase risk of recurrent breast cancer.